Socialization of Product Packaging Efforts to Increase Competitiveness for MSMEs in Tambak Bulak Sidoarjo - Virginia Mandasari; Mentari Clara Dewanti; Fauzatul Laily Nisa; Anisa Fitria Utami (Future Science, 2023)
Food is a basic human need that comes from natural resources and most of it is also produced by home industries which have been processed into various types of food. The high demand for food has become a very important concern for the government to ensure that food is safe for consumption by all consumers. One form of guarantee issued by the government is a PIRT (home industrial food) permit. PIRT is a food production permit produced by home industry scale businesses. This permit is an official letter issued by BPOM (Food and Drug Monitoring Agency). The problem experienced by the